Penghentian Proses Hukum Dalam Penanganan Perkara Dekriminalisasi - Alfons Zakaria (Fakultas Hukum Universitas Mulawarman, 2007)
The implementation of law in society need values which always be obeyed, such as rule of law and justice. However, sometime they cannot be applied simultaneously. The rule of law can be ignored in order to achieve the justice. It can be seen on article 1 verse 2 of Indonesia Criminal Code which disregard principle of legality to give the justice for the offender. In practice, the example case is decriminalization. If an unlawful act is classified as decriminalization, as result all the current cases must be terminated. This article will explain about discontinuing the decriminalization case and the law on each phase of legal process are taken. Key words : dekriminalisasi (decriminalization), keadilan ( justice), proses hukum (legal process).